2011
DOI: 10.1152/japplphysiol.00653.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor function of the upper-airway muscles and respiratory sensory processing in untreated obstructive sleep apnea

Abstract: Numerous studies have demonstrated upper-airway neuromuscular abnormalities during wakefulness in snorers and obstructive sleep apnea (OSA) patients. However, the functional role of sensorimotor impairment in OSA pathogenesis/disease progression and its potential effects on protective upper-airway reflexes, measures of respiratory sensory processing, and force characteristics remain unclear. This study aimed to gain physiological insight into the potential role of sensorimotor impairment in OSA pathogenesis/di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 56 publications
4
66
3
3
Order By: Relevance
“…13 This finding may mirror other UAW muscles alterations in response to our intervention with FP. Interestingly, a more recent study of untreated OSA patients reported a pattern of wakefulness tongue function changes 46 similar to that observed in our study, i.e., these patients, relative to controls, demonstrated greater maximal protrusive force but shorter time to task failure. These functional alterations have as histological substrate a shift from type I (slow twitch-low force, fatigue resistant) to type II (fast twitch-high force, fatigue prone) muscle fibers, 47,48 and are believed to be an adaptive mechanism to the increased contractile demands on the dilator.…”
Section: Changes In the Tongue Function In Response To Fp Therapy Andsupporting
confidence: 90%
See 1 more Smart Citation
“…13 This finding may mirror other UAW muscles alterations in response to our intervention with FP. Interestingly, a more recent study of untreated OSA patients reported a pattern of wakefulness tongue function changes 46 similar to that observed in our study, i.e., these patients, relative to controls, demonstrated greater maximal protrusive force but shorter time to task failure. These functional alterations have as histological substrate a shift from type I (slow twitch-low force, fatigue resistant) to type II (fast twitch-high force, fatigue prone) muscle fibers, 47,48 and are believed to be an adaptive mechanism to the increased contractile demands on the dilator.…”
Section: Changes In the Tongue Function In Response To Fp Therapy Andsupporting
confidence: 90%
“…These functional alterations have as histological substrate a shift from type I (slow twitch-low force, fatigue resistant) to type II (fast twitch-high force, fatigue prone) muscle fibers, 47,48 and are believed to be an adaptive mechanism to the increased contractile demands on the dilator. 46 Was a similar pathology involved in our subjects? Further work needs to be done to answer this question.…”
Section: Changes In the Tongue Function In Response To Fp Therapy Andmentioning
confidence: 98%
“…Raw genioglossus and tensor palatini EMG were rectified, movingtime averaged (100 ms), and expressed as a percentage of maximum activity. 23,24 Peak (maximum during inspiration) and tonic EMG (nadir during expiration), and respiratory parameters were quantified on a breath-by-breath basis using customdesigned semi-automated software as described previously. 25 Upper airway resistance (R UA ) was quantified as the difference in mask versus epiglottic pressure during inspiration at a flow rate of 200 mL/s.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Wakefulness upper airway muscle activity and respiratory parameters were acquired during quiet breathing on and off therapeutic CPAP prior to lights out at approximately 10:30. If required, the CPAP level was increased throughout the night to eliminate any sign of inspiratory flow limitation (according to the epiglottic pressure-flow relationship), yielding the holding pressure.…”
Section: Protocolmentioning
confidence: 99%
“…The respiratory-related evoked potentials (RREPs) during wakefulness in OSA revealed a reduction in the amplitude but not the latency of the early RREP components [44,47] reflecting sensory processing is reduced in the OSA patients [48]. Other studies revealed no changes [49][50][51].…”
Section: Sleep Apnea -Recent Updatesmentioning
confidence: 96%